The Needs Analysis of English for Specific Purposes: A Study in an Indonesian Medical School - Laely Hidayati; Diah Royani Meisani (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
In Indonesian higher education institutions, English has been taught for the past few decades to fulfill the specific academic and professional needs of students. The present study investigates medical students’ needs for English when studying for their medical degrees which indirectly benefits their professional environments. Through survey-based research, this study examined the communication requirements of students at the Faculty of Medicine at both the academic and professional levels. The data collected through an adapted questionnaire were gathered, examined, and statistically interpreted. Three hundred medical, midwifery, and pharmacy students responded. Their answers highlight the importance of English for students' ability to participate in and understand medical discourse and communicate formally in academic settings. Accordingly, the findings of the study should contribute to improving the course objectives and syllabus, so as a result, the study will definitely benefit the learners for whom it is designed.